2000
DOI: 10.1164/ajrccm.161.4.9907147
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Combination Bactericidal Antibiotic Testing for Patients with Cystic Fibrosis Infected with Burkholderia cepacia

Abstract: Most Burkholderia cepacia strains are resistant to many, or all, of the antibacterial agents commonly used in cystic fibrosis (CF), and selection of appropriate antibiotics for treatment of pulmonary exacerbations is therefore difficult. We developed a technique for rapid in vitro testing of multiple antibiotic combinations for B. cepacia isolates. For each of 119 multi-drug-resistant isolates of B. cepacia, our multiple combination bactericidal test (MCBT) studied the bactericidal activity of 10 to 15 antimic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
166
2
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(174 citation statements)
references
References 20 publications
(20 reference statements)
0
166
2
6
Order By: Relevance
“…Innate resistance to antibiotics (31) and an ability to spread from patient to patient (32) make these bacteria especially problematic clinically. As of yet, little is known about virulence determinants that make BCC particularly virulent for CF and CGD patients, whereas posing little or no threat to the population in general (2).…”
Section: Discussionmentioning
confidence: 99%
“…Innate resistance to antibiotics (31) and an ability to spread from patient to patient (32) make these bacteria especially problematic clinically. As of yet, little is known about virulence determinants that make BCC particularly virulent for CF and CGD patients, whereas posing little or no threat to the population in general (2).…”
Section: Discussionmentioning
confidence: 99%
“…There is a general consensus that isolates identified through commercial test systems as belonging to the B. cepacia complex, Step 2: repeat step 1 for 5 days 105 . In a study on 119 multi-drug resistant B. cepacia isolates, multi combination bactericidal testing (mcbt) showed that triple antibiotic combinations containing tobramycin, meropenem and a third additional antibiotic were most effective 106 . These combinations were bactericidal against 81-93% of isolates.…”
Section: Burkholderia Cepacia Complexmentioning
confidence: 99%
“…However, some pathogenic strains of B. cepacia are resistant to above drugs combination and are difficult to treat. So, other treatment modalities must be adopted like multiple combination bactericidal therapy to assess whether greater effect can be achieved when more than two drugs are given together [7]. Recently, an alternate system called biofield treatment is reported to alter the susceptibility of microorganism towards existing medicines [8].…”
Section: Introductionmentioning
confidence: 99%